Prevalencia de Balantidium coli en la población humana y porcina asociado a factores socioeconómicos y saneamiento ambiental en el Distrito de Acora Puno Perú - Condemayta, Zacarías (2018)
In order to determine the prevalence of B.coli in the human and porcine population and its association with socioeconomic factors and environmental sanitation, 221 human faecal samples (children and adults) and 80 fecal swine samples (young and adult) were taken. from the populated centers of Socca ("lake zone") and Caritamaya ("intermediate zone") of the district of Ácora, province and department of Puno in Peru; These samples were subjected to parasitological analysis in the Veterinary Parasitology Laboratory of the Faculty of Veterinary Medicine and Zootechnics, National University of Altiplano, in Puno. In order to identify the epidemiological factors associated with balantidiasis, a survey was applied to 100 adults from the two areas mentioned. In order to compare the prevalence of B. coli between children and adults; between young and adult pigs and between the two zones, the Chi-square test was applied and to identify the epidemiological factors associated with balantidiasis, the Chi-square test of Pearson's association, using the software SPSS version v23 was applied. The following results were obtained: The prevalence of Balantidium coli in the human population was 5.88%; 6.60% in children and 5.00% in adults; 8.1% in the "lake zone" and 3.6% in the "intermediate zone".  The prevalence of the parasite in the pig population was 88.75%; 91.67% in young animals and 84.38% in adults; 90.00% in the "lake zone" and 87.50% in the "intermediate zone"; there is no difference in the prevalence of protozoa between children and adults, similarly between the human population of these two zones, as well as between young pigs and adults, also between pigs from both zones. With regard to the association of balantidiasis and socioeconomic factors and environmental sanitation; the disease was associated with the adult age of the people and the use of latrines and other epidemiological factors, which were not associated with balantidiasis. In conclusion, in the Acora area, the prevalence of B. coli in the human population was low and in the porcine population it was high; and the ailment was limited by the adult age of the people and the use of latrines.